Perilaku guru SMA Frater Don Bosco Manado dalam pencegahan kekerasan terhadap perempuan - Latun, Erick; Rombot, Dina Victoria; Siagian, Iyone E. T. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Objective: To describe the behavior of teachers to prevent violence against women. Methods: Qualitative descriptive with grounded theory approach, conducted by focus group discussion and in-depth interview. The research was conducted in Don Bosco Senior Highschool Manado with 10 informants both male and female undergo focus group discussion. Later on, 4 informant were selected based on their answers for in-depth interview. The result were turned in matrices and drawn the conclusions based on Miles and Hubberman qualitative data analysis. Results: The teachers tendency on prevent violence against women was conduted in the classroom while teaching. Shaping the mindset towards gender equality in form of advices and counseling by taking few minutes from the subjects. Conclusion: Three years on highschool isn t enough for both teachers and students to establish the gender equality mindsets. It may take more research about the correlation between earlier age intervention and the success rate to establish the mindset of gender equality.